2008
DOI: 10.1007/s12197-008-9070-2
|View full text |Cite
|
Sign up to set email alerts
|

Income smoothing and foreign asset holdings

Abstract: In this paper we construct a new methodology to measure the international income smoothing and present stronger connection between international asset holding and international income smoothing for OECD countries.JEL classification: F155, F36, F41

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Balli et al (2010b) andBalli et al (2011) also followedSørensen et al (2007) and found that the extent of income smoothing through net factor income flows and the amount of the foreign asset holdings do not have a strong relationship.…”
mentioning
confidence: 99%
“…Balli et al (2010b) andBalli et al (2011) also followedSørensen et al (2007) and found that the extent of income smoothing through net factor income flows and the amount of the foreign asset holdings do not have a strong relationship.…”
mentioning
confidence: 99%